A review of studies on teachers’ written corrective feedback - Hieu`, Do Manh; Huong, Phan Le Thu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2020)
This paper provides an overview of available research findings of Written Corrective Feedback (WCF) studies conducted in various contexts including Vietnam. It is recognized that researchers have paid attention to two key areas which are the effects of WCF and students’ perceptions on WCF. Although students have different perceptions on different types of feedback (direct or indirect feedback), they all show positive attitudes toward WCF because it assists them to improve their writing. Finally, research gaps and suggestions are discussed and presented at the end of the paper.